Representasi Seksisme dalam Film Kim Ji-Young: Born 1982 - Herlambang, Mochamad (Universitas Brawijaya, 2022)
Kim Ji-Young: Born 1982 is a gender role-themed film that raises the issue of sexism against women in South Korea. This study seeks to answer research questions about how sexism is represented in the Kim Ji-Young: Born 1982 film. The type of this research is descriptive qualitative with a critical paradigm and uses Roland Barthes' semiotic research method to find out the denotations meaning, connotations meaning and myths that are formed about sexism in the film Kim Ji-Young: Born 1982. The results of this research indicate that women are depicted as a figure identified with domestic work, girls who are considered not to have more value than boys, women that are considered as figures who must serve men, women that are considered to be less competent than men in the workplaces, women that are considered to have a limited role as a caregiver, women that are considered weaker and helpless, and women who are also considered as sexual objects only.